Percutaneous transluminal angioplasty and stenting in the management of chronic mesenteric angina: A single center experience - Thomas, Tixon (Indian J Radiol Imaging, 2016)
INTRODUCTION: The objective of our study was to review the results of percutaneous angioplasty (PTA)/stenting in the treatment of patients who presented with symptoms and angiographic findings of chronic mesenteric ischemia (CMI). MATERIALS AND METHODS: We performed a retrospective analysis of 13 consecutive patients from a single institution who underwent PTA/stenting for the treatment of symptoms suggestive of CMI. RESULTS: All 13 patients in our study were men, and most common presenting symptoms were weight loss and postprandial pain. Atherosclerosis was the most common cause. PTA and stenting was performed in 9 patients and PTA alone was done in 4 patients. Primary technical success rate was 92% with complete resolution of symptoms within 2 weeks in all patients. No statistical difference was noted in primary clinical success rate based on the number of vessels treated or the method of treatment. However, in patients whom SMA was treated had longer duration of symptom-free survival as compared to other vessels. CONCLUSION: PTA and stenting are very effective therapeutic options for patients presenting with CMI symptoms. It should be considered as the first-line of management in such patients.